Utilization of Milk By-Product (Buttermilk) in the Preparation of Chhurpi and its Quality Evaluation - Shrestha, Som Raj; Pradhananga, Mahalaxmi; Das, Suman Kumar Lal (Sunsari Technical College Journal, 2016)
Chhurpi, a traditional milk product were prepared with slight improvement in manufacturing practice; using skim milk: butter milk at different variations (SM:BM=0:100, 20:80, 40:60, 60;40. 80:20, and100:0) at 70ºC and coagulated by 2% tartaric acid maintaining pH value 5.3. The formulation having ratio SM:BM of 0:100 found to be best among all the formulations except the control one and was not significantly different in terms of flavor, body and texture, gumminess and chewiness and overall acceptability. Physico– chemical analysis of best product was found to be 10% moisture, 5.26% fat, 74.17% protein, 3.18% lactose and 6.26% total ash. Chemical analysis of the best product was not significantly different in terms of lactose content and total ash content while it was significantly different in terms of moisture content, fat content and protein content from control i.e. 100% skim milk at p<0.05. Hence, according to this research the sweet cream buttermilk as a waste of dairy industries can be solely used to convert into a value added milk product with earnings. Sunsari Technical College Journal 2015,2(1):1-6